Avisalmvac: evaluation studies of stability and toxicity - Daniela Botus,; Virgilia Popa,; Bucur, E.,; Caplan, E.,; Pirvulescu, M.,; Belteghi, C.,; Pastrama, F. (Medicamentul Veterinar)
In Pasteur Institute laboratories there was developed AVISALMVAC, a vaccine against avian Salmonella, a biological product that contains S. enteritidis and S. typhimurium bacterin, with oil adjuvant. This paper presents the results of the studies regarding the stability and toxicity evaluation of this vaccine stored under conditions recommended by the manufacturer (2-80C) at the end of the period of validity. The vaccine stability was assessed by serological and histopathological analysis of samples from SPF chickens vaccinated with the product at the end of the period of validity. The study of Avisalmvac toxicity was carried out by inoculation of the product or its components on Vero cell monolayer, and the effects were microscopically recorded or by MTT test, applied at 6 days post-inoculation. Antibody titers recorded at 2 and 3 weeks post vaccination demonstrated the vaccine ability (used after an year since manufacture) to induce synthesis of specific antibodies and therefore, the product stability was proven. Histopathological examinations carried out on samples taken at 18 days post vaccinationfrom the vaccination site (skeletal muscle and skin) and spleen, did not show any lesions associated to vaccination with Avisalmvac. The cytotoxicity analysis made by inoculating the vaccine or its components on Vero cell monolayer and the microscopic examination did not record visible cytopathic effects for any vaccine dilutions or vaccine components. The cell metabolism evaluation by MTT assay made at 6 days after vaccine/vaccine components inoculation on Vero monolayer, shown the ability of the vaccine and oil adjuvant to stimulate cell metabolism, and a certain degree of toxicity / inhibition of dehydrogenase metabolism associated to one of emulsifier but at dilutions higher than those used in the vaccine formula.